PENGARUH STRUKTUR MODAL, RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP PAJAK PENGHASILAN (PPh) BADAN “STUDI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2015 – 2017 - Putri Hayyatus Sholihah; Jeni Susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRAC This research was conducted to analyze the Effect of Capital Structure, Return on Equity (ROE) and Earning per share (EPS) on Corporate Income Tax (PPh). The sample in this study is a manufacturing company in 2015-2017 which is included in the consumer goods industry sub-sector. The analytical method used is multiple linear regression with SPSS 20 software for windows. The results of the sampling using the purposive sampling method resulted that the consumption goods manufacturing sub-sector companies listed consecutively on the IDX in 2015-2017 and fulfilled the sample criteria were 23 companies. Based on the results of hypothesis testing that has been done, it is concluded that simultaneously Capital Structure, Return on Equity (ROE) and Earning per share (EPS) affect the Corporate Income Tax (PPh). The variables Debt To Asset Ratio, Debt To Equity Ratio and, Return on Equity affect the Corporate Income Tax (PPh). While the variable Earning per share partially does not affect the Corporate Income Tax (PPh). Keywords : Capital Structure, Return on Equity (ROE) and Earning per share (EPS) of Corporate Income Tax (PPh).